Laboratory investigation on the mechanical behavior of asphalt mixtures incorporating reclaimed asphalt pavement (RAP) and Sasobit additive - Mohammed, Humam H. (Edelweiss Applied Science and Technology, 2025)
The serious rutting problem faced by asphalt pavements requires authorities to create better-performing asphalt mixtures that address this issue. The research examines how adding Sasobit warm mix additive to asphalt mixtures, which combine 30% reclaimed asphalt pavement (RAP), affects their Marshall properties, moisture damage, and rutting resistance. Tests were conducted with Sasobit at three different addition rates: 1%, 2%, and 3%. Experimental results show that adding 2% Sasobit to a mixture containing 30% RAP resulted in the best Marshall characteristics, with a maximum stability measurement of 12.2 kN and better performance than the control mixture, which had 9.8 kN stability. The 2% Sasobit mixture displayed the lowest flow rate at 2.9 mm, while the control mixture flowed at 3.3 mm. The best rutting resistance performance appeared in the mixtures of 2% Sasobit with 30% RAP, reducing the unmodified mix's rut depth by 44%. Adding 2% Sasobit into mixture samples decreased moisture damage by 8.5% compared to the unmodified samples in moisture susceptibility tests. The results indicate that optimal Sasobit concentrations improve the durability, stability, and resistance of asphalt mixtures containing recycled asphalt pavement while extending their usefulness for road construction.